Association between expression of ZBP1, AIM2, and MDA5 genes and severity of COVID-19 - Nasir Arefinia; Amin Ramezani; Mehrdad Farokhnia; Ali Mohammad Arab Zadeh; Ramin Yaghobi; Jamal Sarvari (EXCLI Journal : Experimental and Clinical Sciences, 2022)
Antiviral and inflammatory responses following the detection of the virus genome by nucleic acid sensors play a vital role in the pathogenesis and outcome of diseases. In this study, we investigated the ZBP1, AIM2, and MDA5 expression levels in COVID-19 patients with different intensities of the disease. 75 quantitative Real-Time PCR (qRT-PCR)-confirmed COVID-19 patients were included consecutively and divided into 3 groups of mild, severe, and critical based on the severity of the disease. Also, 25 healthy volunteer subjects were included. PBMCs were collected from the whole blood, and RNA was extracted using commercial kit. The expression of ZBP1, AIM2, and MDA5 genes was investigated using qRT-PCR technique. The mean age of the patients and healthy volunteers was 52.73±13.78 and 49.120±12.490, respectively. In each group, 13 out of 25 participants were male. The expression levels of ZBP1 (P=0.001), AIM2 (P=0.001), and MDA5 (P= 0.003) transcript were significantly higher in COVID-19 patients than the control group. The results also revealed that the expression levels of ZBP1, AIM2, and MDA5 were significantly higher in the critical and severe COVID-19 patients compared to those with mild disease (P<0.05). Moreover, regarding the gender, the expression levels of AIM2 and MDA5 were significantly elevated in male severe (P=0.04 and P=0.003, respectively) and critical (P=0.005 and P=0.0004, respectively) patients than the female ones. The results indicated that ZBP1, AIM2, and MDA5 genes might have an important role in the severity of COVID-19 disease. Moreover, the severity of COVID-19 disease in male and female patients might be related to AIM2, and MDA5 expression levels. More studies are recommended to be conducted to clarify this issue.